2019
DOI: 10.1038/s41598-018-38101-5
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional CT as a valid approach to detect and quantify kinematic changes after selective ankle ligament sectioning

Abstract: The objective of the current study was to explore the potential of dynamic computed tomography to detect kinematic changes, induced by sequential sectioning of the lateral collateral ligaments of the ankle, during full motion sequence of the talocrural joint. A custom-made device was used to induce cyclic controlled ankle inversion movement in one fresh frozen cadaver leg. A 256-slice CT scanner was used to investigate four different scenarios. Scenario 1 with all ligaments intact was first investigated follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…been reported. Recent studies have shown the potential of four-dimensional (4D) CT to evaluate subtalar joint kinematics and detect changes between healthy and pathological subjects both ex vivo 36 and in vivo 37 . However, all previous literature reports images acquired with subjects placed in the CT scanner table in a supine position and, although custom-built ankle loading devices are commonly used, images acquired are not in a weight-bearing configuration. During weight-bearing, the combination of tensile loading of the ligaments and compression loading of all the joints of the foot creates a more tightly joined and stable architecture when compared to a non-weight-bearing situation 19 .…”
mentioning
confidence: 99%
“…been reported. Recent studies have shown the potential of four-dimensional (4D) CT to evaluate subtalar joint kinematics and detect changes between healthy and pathological subjects both ex vivo 36 and in vivo 37 . However, all previous literature reports images acquired with subjects placed in the CT scanner table in a supine position and, although custom-built ankle loading devices are commonly used, images acquired are not in a weight-bearing configuration. During weight-bearing, the combination of tensile loading of the ligaments and compression loading of all the joints of the foot creates a more tightly joined and stable architecture when compared to a non-weight-bearing situation 19 .…”
mentioning
confidence: 99%
“…This technique does not utilise 3D volume rendering technology, and has a higher associated error rate than the technique outlined in this study. More recently, 4D CT has been used in cadaveric studies of the ankle to quantify kinematic changes following ligament sectioning [23]. Similarly, there have been other studies focused on scapholunate instability and calculating angles using 4D-CT [24].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic computer tomography (4D-CT) enables acquisition of a series of high temporal-resolution 3D CT datasets of moving structures. Various phantom studies [6][7][8][9] demonstrated the validity and feasibility of dynamic CT for evaluating MSK diseases. Several patient studies have been conducted investigating different joint disorders of the wrist, knee, hip, shoulder and foot [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have proposed methods to account for sliding motion [16,17], but most rely on prior segmentations of bones of interest. Motion estimation of MSK structures is therefore commonly performed using prior manual segmentations of the bony structures, limiting registration to a region of interest and obtaining individual bone motion to facilitate estimation of kinematics [6,8]. However, manual bone segmentation is labor intensive and hinders application in clinical routine.…”
Section: Introductionmentioning
confidence: 99%